Strategi Komunikasi Penggunaan Instagram dalam Meningkatkan Kesadaran Masyarakat akan Krisis Iklim - Junaidi, Ahmad; Syaifurahman, Budi (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
Indonesia is experiencing environmental problems such as air pollution, illegal logging, waste, that cause natural damage. There have been many social media campaigns for the declaration of